2018
DOI: 10.1111/imig.12513
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dimensions of Migration on Union Dissolution

Abstract: This investigation uses data from Nicaragua to evaluate the temporal and geographic influences of migration on union dissolution. We investigate the impact of three migration types: internal (within Nicaragua), South-South international (to Costa Rica), and South-North international (to the United States). We perform event history analyses using data from the Latin American Migration Project (LAMP) to test whether longer migrations (time) and migration to international and more distant locations (place), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The following literature review is limited to such studies, which are sparse and show mixed results. International migration of men from different Latin American countries increased the risk of union dissolution (Frank & Wildsmith, 2005; Lindstrom et al, 2021), but a study on Nicaraguan men found elevated dissolution risks only for internal migrants or a longer migration duration (independent of the destination) (Davis & Jennings, 2018). Studies focussing on internal migration only found enhanced (Shapira et al, 2019) or similar dissolution risks (Boyle et al, 2008) among long‐distance movers, but dissolution risks among short‐distance movers were decreased (Boyle et al, 2008; Shapira et al, 2019).…”
Section: State Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The following literature review is limited to such studies, which are sparse and show mixed results. International migration of men from different Latin American countries increased the risk of union dissolution (Frank & Wildsmith, 2005; Lindstrom et al, 2021), but a study on Nicaraguan men found elevated dissolution risks only for internal migrants or a longer migration duration (independent of the destination) (Davis & Jennings, 2018). Studies focussing on internal migration only found enhanced (Shapira et al, 2019) or similar dissolution risks (Boyle et al, 2008) among long‐distance movers, but dissolution risks among short‐distance movers were decreased (Boyle et al, 2008; Shapira et al, 2019).…”
Section: State Of Researchmentioning
confidence: 99%
“…Besides the general effect, several migration characteristics have been found to affect the risk of union dissolution. These include the length of geographic separation when assessing individual's migration (Davis & Jennings, 2018; Frank & Wildsmith, 2005), its direction (rural–urban or different destinations) (Boyle et al, 2008; Davis & Jennings, 2018), the prevalence of migration at the community level (Frank & Wildsmith, 2005), as well as the migration decision and whether both partners moved at the same time or not (Baykara‐Krumme et al, 2021). Referring to the migration characteristics of analysis in this study, multiple (internal) migrations were found to increase the risk of union dissolution (Boyle et al, 2008; Muszynska & Kulu, 2007; Shapira et al, 2019).…”
Section: State Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In research on the effects of international migrations, a main focus is on transnationally separated couples and their union dissolution risks in this specific situation. For instance, Davis and Jennings (2018) found for ever-married emigrant men from Nicaragua that migration and a separation from their spouses, and even more importantly, the duration of the separation increases the dissolution risk. Previously, the widespread migrant narrative of "the spousal desertion" triggered research on Mexican couples by Frank and Wildsmith (2005), who found that shorter separations do not increase divorce risks compared to non-migrants, but longer stays abroad do increase risks.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…For example, Cooke, Boyle, Couch & Cooke, Boyle, Couch & Feijten (2009) submit that divorce amplifies gender pay gaps and differences in human capital. Thomas et al (2017) expand the notion of human capital inequalities by observing how women operate in more restricted labour markets and are less likely to operationalise human capital than men (Agadjanian & Hayford, 2018;Bradbury & Katz, 2002;Davis & Jennings, 2018;Kang, Song, Kim, & Sohn, 2009;Killewald, 2016;Smits et al, 2003). Additionally, studies have explored the notion that resource inequalities between genders may be a product of educational attainment differences, and that personal development sacrifices made by women in pursuing marriage can lead to a resource deficit compared to male partners (Cooke et al, 2009;Thomas et al, 2017).…”
Section: Gendermentioning
confidence: 99%